The gut microbiota and post-traumatic major depression disorder: insights from bidirectional two-sample Mendelian randomization - Liu, Shan; Wang, Yu; Zhang, Yonghu; Zeng, Liang; Ling, Lin; Luo, Yong; Liu, Wenjie (Frontiers in Psychiatry, 2024)
Background: Exposure to trauma is often associated with an increased incidence of Major Depressive Disorder (MDD), yet the mechanisms underlying MDD development post-trauma remain elusive. The microbiota-gut-brain axis has been implicated in neuropsychiatric disorders, suggesting its potential role in post-traumatic MDD (PTMDD) development. Our study aimed to assess the significance of the gut microbiome-brain interaction in PTMDD.We conducted a bidirectional two-sample Mendelian Randomization (MR) analysis to investigate the causal relationship between the gut microbiota and both PTMDD and trauma exposure in MDD. Genome-wide association study (GWAS) summary datasets for PTMDD and trauma exposure in MDD, both derived from the UK Biobank. The PTMDD dataset included 24,090 individuals (13,393 cases and 10,701 controls), while the dataset for trauma exposure in MDD comprised 22,880 participants (13,393 cases and 9,487 controls) . Additionally, gut microbiota data from the MiBioGen consortium included 14,306 European individuals across 18 diverse cohorts.Results: Our research identified a significant negative association between the phylum Verrucomicrobia (odds ratio (OR) [95% confidence interval (CI)] =0.799 [0.684-0.933], P=0.005) and the risk of developing PTMDD, suggesting a protective role for Verrucomicrobia against PTMDD. Conversely, our findings indicate no causal effects of the gut microbiota on trauma exposure in MDD. However, reverse analysis revealed that both PTMDD and MDD influence certain bacterial traits, affecting 5 and 9 bacterial traits, respectively.Moreover, Verrucomicrobia (OR [95%